THE ROLE OF ETHNIC POLES IN INDUSTRIAL BEEKEEPING DEVELOPMENT OF SLOBOZHANSHCHINA AT THE PERIOD OF IT’S SOCIAL-ECONOMIC MODERNIZATION IN THE SECOND HALF OF THE ХІХ – AT THE BEGINNING OF THE XX CENTURY - Трубчанінов, Микола (SWorldJournal, 2023)
The article investigates the development of the industrial beekeeping in Slobozhanshchyna country households which was widespread in the second half of the XIX - at the beginning of the XX century. The main attention is paid to the characteristics of the